Generation of lymphokine-activated killer cell activity from non-NK precursor cells - Ramsdell, F J; Lindemann, R A; Shau, H Y; Gray, J D; Golub, S H (Cellular immunology, 1988)
It is possible to generate high levels of lymphokine-activated killer (LAK) activity in short-term culture from cells enriched for natural killer (NK) activity. To determine whether LAK activity can also be generated from non-NK cells, we have depleted peripheral blood lymphocytes (PBL) of NK cells prior to culture with IL-2. NK activity in PBL is correlated with the intensity of staining with the lysosomotropic vital dye quinacrine. Quinacrine dim PBL, which are devoid of lytic NK cells, are capable of developing LAK activity following culture with IL-2. We have also separated PBL using the NK-associated NKH-1 marker. Depleting NKH-1+ cells eliminates NK activity but the ability to develop LAK activity is retained. NKH-1-depleted cells generate less LAK activity than unseparated or NKH-1-positive cells and do not proliferate as well as unseparated cells to IL-2. When NK-depleted cells are subsequently examined for the expression of the NKH-1 antigen, this marker is absent from most cells at Day 3 of IL-1 culture, but is expressed on an increasing number of cells by Days 6-8. These results suggest that LAK derived from non-NK cells is functionally and phenotypically similar to LAK from PBL-containing NK cells, and may be the result of the activation of an NK precursor population.